Whole Genome Sequencing detects Inter-Facility Transmission of Carbapenem-resistant Klebsiella pneumoniae. Issue 3 (March 2019) - Spencer, Melanie D.; Winglee, Kathryn; Passaretti, Catherine; Earl, Ashlee M.; Manson, Abigail L.; Mulder, Holly P.; Sautter, Robert L.; Fodor, Anthony A.
Highlights: A K. pneumoniae outbreak resulted in unexpected spread beyond the primary hospital. Whole genome sequence analysis was crucial to detect complex transmission patterns. K. pneumoniae silent colonization was a major factor in inter-facility transmission. Results underscore complexity of K. pneumoniae prevention and management. Summary: Objectives: To identify transmission patterns of Carbapenem-resistant Klebsiella pneumoniae infection during an outbreak at a large, tertiary care hospital and to detect whether the outbreak organisms spread to other facilities in the integrated healthcare network. Methods: We analyzed 71 K. pneumoniae whole genome sequences collected from clinical specimens before, during and after the outbreak and reviewed corresponding patient medical records. Sequence and patient data were used to model probable transmissions and assess factors associated with the outbreak. Results: We identified close genetic relationships among carbapenem-resistant K. pneumoniae isolates sampled during the study period. Transmission tree analysis combined with patient records uncovered extended periods of silent colonization in many study patients and transmission routes that were likely the result of asymptomatic patients transitioning between facilities. Conclusions: Detecting how and where Carbapenem-resistant K. pneumoniae infections spread is challenging in an environment of rising prevalence, asymptomatic carriage and mobility of patients. Whole genome sequencing improved the precision of investigating inter-facility transmissions. Our results emphasize that containment of Carbapenem-resistant K. pneumoniae infections requires coordinated efforts between healthcare networks and settings of care that acknowledge and mitigate transmission risk conferred by undetected carriage and by patient transfers between facilities.